How to Improve the Continuous Usage of Mobility Apps - The Effects of Personalisation and Privacy on the Use of Mobility Applicationsin German Urban Areas - Arjan Vlaskamp (Marketing Review St.Gallen, 2023)
Even though mobile apps are becoming more important in the marketing mix, not much research has been done on what makes people decide to use an app or not. This paper presents a new valuebased technology adoption model and investigates whether the perceived value of a mobility app influences the user's intention to continue using the service.
Keywords: 650